Hour of the Olympics - Osborne, Mary Pope. (New York : Random House, 1998)
Their magic tree house takes Jack and Annie back to retrieve a lost story in ancient Greece, where they witness the original Olympic games and are surprised to find what girls of the time were not allowed to do.
"A Stepping Stone book."
"RL:2.3"--cover p. [4].
2-3
Keywords: Olympics -- Fiction; Time travel -- Fiction; Sex role -- Fiction; Magic -- Fiction; Tree houses -- Fiction; Greece -- Fiction